0030 Making your worklife easier: resources and tools to efficiently respond to injury data requests. (26th April 2015) - Proescholdbell, Scott; Hedegaard, Holly; Johnson, Renee; Dao, Dan; Hume, Beth; Brutsch, Elizabeth
Abstract : Statement of purpose: Fulfilling injury data requests has become increasingly challenging due to the complexity of injury topics (e.g., drug overdose) and the scale of requests (e.g., State Injury Indicators and Special Emphasis Reports). This panel presentation will provide brief demonstrations, resources, tools and examples of how to successfully respond to injury data requests, as well as provide tips for using data in grant writing and to inform prevention programs, decision-makers, the media and others. Methods/Approach: A panel member from the National Centre for Health Statistics (NCHS) will provide an overview and demonstration of several national on-line query tools, including CDC WONDER, the NCHS Health Indicators Warehouse and WISQARS. Staff from CDC's National Centre for Injury Control will provide an overview of the CDC State Injury Indicators and Special Emphasis Report Tools. Representatives from states that successfully submit data/reports will provide examples of how they process these requests and lessons learned. State representatives will share examples of data quality improvement projects, including the Standardised Data Set Project and CDC funded projects for Surveillance Quality Improvement. Results: By the end of this session, participants will: 1) be aware of on-line systems for rapid query of injury data, 2) understand the tools available from CDC to assist in the preparation of the State Injury Indicators and Special Emphasis reports, 3) learn from states about how to efficiently generate reports and maximise their utility for multiple audiences, 4) see examples of ways to assess and improve the quality of injury data, and 5) learn about tools to test and improve analysis methods for accurate and consistent results. Conclusions: State and local health departments frequently receive requests for injury data and reports. The goal of this session is to provide tools, resources, examples and lessons learned so that any state injury program can readily respond to such data requests. Significance and contribution to the field: Awareness of the tools and resources to efficiently respond to injury data requests will ease the burden on state injury prevention programs.